A STUDY OF NEUTROPHIL LYMPHOCYTE-TO-ALBUMIN RATIO TO PREDICT SHORT-TERM MORTALITY IN ALCOHOL-RELATED LIVER DISEASE - SACHIN PATIL; KOTLI NAGARAJ; NIVEDITA M TAYAMGOL; HEMANTH REDDY NUKALA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aims of this study were as follows: (1) to study neutrophil lymphocyte-to-albumin ratio (NLAR) in alcohol-related liver disease patients to predict 30-day mortality and (2) to determine the optimal cutoff value of the NLAR that maximizes sensitivity and specificity for predicting short-term mortality. Methods: A prospective study conducted at our hospital for 18 months. A total of 46 males visiting the medicine OPD and IPD were included in the study. Blood samples were collected to measure neutrophil, lymphocyte, albumin levels were measured using standard methods. Data were analyzed using appropriate inferential statistics Results: The majority of participants fall within the 31–40 age group (26.1%), followed by the 41–50 age group (23.9%). The majority of participants were diagnosed with cirrhosis of the liver (65.2%), while alcoholic hepatitis (AH) and fatty liver disease were both observed in 17.4% of the participants. The outcomes at 30 days a significant majority of the cases resulted in death (65.2%), with only 34.8% of the cases being followed up. We observe that for NLA, the cutoff value is observed to be 19.15 with a sensitivity of 100% and specificity of 100%. There is a significant mean difference observed for Hemoglobin, total count, neutrophil, lymphocyte, urea, INR, total protein, albumin, and NLA. Conclusion: A cutoff value of 19.15 for the NLAR is identified as highly sensitive and specific, highlighting its clinical significance as patients with an NLA ratio above this threshold have a high probability of death within 30 days.